Decisions and Authority of The Religious Courts on Sharia Economic Disputes - Witro, Doli (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2021)
This article discusses one of the court products focused on the verdict. The presentation of the decision is divided into three sub-discussions, namely the understanding of court decisions, types and developments of court decisions in sharia economic cases, and legal remedies against sharia economic decisions. This article aims to find out how the decisions of Religious Courts regarding sharia economic disputes are used. The method used in this article is normative juridical, which is carried out qualitatively. The materials in this article come from laws, decisions of the Constitutional Court, decisions of the Supreme Court, books, scientific articles from journals, internet websites and so on related to the theme being studied, namely Religious Court decisions on sharia economics disputes. The data analysis technique used content analysis techniques. The results of the analysis show that the court’s decision is the final result or conclusion in written form, which is decided by a state official (judge) who is given the authority to end or settle a lawsuit because there is contention between the disputing parties in court which must be submitted in a hearing.